Strategi Efektif Mengatasi Tantangan Dalam Mengelola Karateristik Siswa Di Kelas 4 SD Kanisius Wonogiri - adithia santi, puja (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2022)
This research is motivated by the diversity of characteristics possessed by students in a class at Elementary School (SD). This diversity of characteristics poses a problem that teachers must address in the learning process. Various characteristics become a problem in managing them. The purpose of this research is to outline strategies for overcoming challenges in managing the characteristics of students. This research was conducted at SD Kanisius Wonogiri, Wonogiri District, Wonogiri Regency. Data collection in this qualitative research was done using several techniques, namely through observation and interviews. Observation was carried out by directly observing the characteristics of fourth-grade students during the learning process. Data collection was conducted through interviews with the Fourth Grade Teacher at SD Kanisius Wonogiri. The results of this research explain the various challenges faced by a teacher in managing the characteristics of fourth-grade students. These challenges encompass differences in learning abilities, varying levels of concentration, and handling large class sizes. When dealing with such complex challenges, teachers need to develop effective strategies to address these student characteristics. Some strategies that teachers can employ include treating children fairly, providing good interaction, and motivating students. These strategies are considered effective in addressing these challenges. This strategy will play a role in the learning process carried out by teachers in the classroom.